2012
DOI: 10.1155/2012/309231
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Green Tea Consumption on Cardiometabolic Alterations Induced by Experimental Diabetes

Abstract: We evaluated cardiac autonomic modulation by heart rate (HRV), and arterial pressure variability (APV), and metabolic response in streptozotocin diabetic rats treated with green tea. Male Wistar rats were separated in groups: control, drinking tap water (C), green tea-treated (GT) group, diabetic, drinking tap water (D), and diabetic, treated with green tea (DGT). Kidney mass was greater in D and DGT than in C and GT, but reduced in DGT compared to D. Green tea prevented the increase in creatinine clearance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…In our work, although WTEA consumption by prediabetic rats did not restore blood glycaemia to control values, it improved glucose tolerance and insulin resistance. It has been reported that GT consumption and/or administration ameliorates glucose metabolism in diabetic individuals (Babu, Sabitha, Srinivasan, & Shyamaladevi, 2007;Fiorino et al, 2012;Tang et al, 2013). The normoinsulinaemia effect and glucose metabolism improvement caused by tea consumption has been attributed to the antioxidant properties of tea.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, although WTEA consumption by prediabetic rats did not restore blood glycaemia to control values, it improved glucose tolerance and insulin resistance. It has been reported that GT consumption and/or administration ameliorates glucose metabolism in diabetic individuals (Babu, Sabitha, Srinivasan, & Shyamaladevi, 2007;Fiorino et al, 2012;Tang et al, 2013). The normoinsulinaemia effect and glucose metabolism improvement caused by tea consumption has been attributed to the antioxidant properties of tea.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, green tea catechins could protect kidney function by reducing the permeability of glomerular filtration membrane through inhibiting thrombosis with lowered microsomal phospholipase A2 and regulating arachidonic acid cascade system [42]. An in vivo study also found that green tea could improve glomerular filtration and reduce the rate of creatinine increase and renal hypertrophy [77]. Further, in diabetic spontaneously hypertensive rats (SHRs), green tea prevented podocyte apoptosis and albuminuria by rising p-low-density lipoprotein receptor-related protein 6 (p-LRP6) expression and blocking glycogen synthase kinase 3 interaction with p53 (GSK3-p53) [78].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Cardiovascular complications, containing cardiomyopathy, atherosclerosis, coronary ischemia, and vascular disease, are associated with the high morbidity and mortality of diabetes mellitus [77,88], among which cardiomyopathy is responsible for 80% [17]. It was reported that tea could improve cardiovascular complications by decreasing hyperglycemia, adjusting lipid metabolism, activating signaling pathways, down-regulating the inflammatory factors, and so on.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggested that administration of green tea or its main constituents by different routes, in various doses, and in different length of time lowered the blood glucose level in type 1 induced diabetic animals [41,56,[66][67][68][69].…”
Section: Hypoglycemic Effect Of Green Tea In Diabetes Mellitusmentioning
confidence: 99%